2021
DOI: 10.21037/tau-19-672
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Y chromosome microdeletions on in vitro fertilization outcomes, health abnormalities in offspring and recurrent pregnancy loss

Abstract: Male factor infertility accounts for approximately 50% of all infertility evaluations. A common cause of severe oligozoospermia and azoospermia is Y chromosome microdeletions (YCMs). Men with these genetic microdeletions must typically undergo assisted reproductive technology (ART) procedures to obtain paternity. In this review, we performed a thorough and extensive search of the literature to summarize the effects of YCMs on in vitro fertilization (IVF) outcomes, health abnormalities in offspring and recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 75 publications
1
7
1
Order By: Relevance
“…Although the effect of AZF deletions on fertilisation rate and embryo quality has been demonstrated in many studies, 34–36 the literature has been contentious on whether they affect miscarriage rates and live birth rates. The findings of our study have disagreed with some previous studies 37,38 and agreed with others 39–41 . Given this continuous inconsistency of results, a prospective multi‐centre study would provide further clarity as to whether these outcomes are affected in AZF‐deleted men compared with AZF‐intact men.…”
Section: Discussioncontrasting
confidence: 92%
“…Although the effect of AZF deletions on fertilisation rate and embryo quality has been demonstrated in many studies, 34–36 the literature has been contentious on whether they affect miscarriage rates and live birth rates. The findings of our study have disagreed with some previous studies 37,38 and agreed with others 39–41 . Given this continuous inconsistency of results, a prospective multi‐centre study would provide further clarity as to whether these outcomes are affected in AZF‐deleted men compared with AZF‐intact men.…”
Section: Discussioncontrasting
confidence: 92%
“…Non-invasive indicators such as age, testicular size, and reproductive hormones, as well as invasive testicular biopsies, are important in determining the spermatogenic function of the testes before micro-TESE and can assist clinicians and infertile couples in making the best clinical decisions for them [13]. A study suggested that spermatogenic function declines with age in patients with AZFc deletion and that early assisted reproduction or sperm freezing is recommended for patients with AZFc deletion [14]. However, our study focused on NOA patients with AZFc deletion, and the results showed that age did not affect SRR by micro-TESE.…”
Section: Discussionmentioning
confidence: 99%
“…Y chromosome microdeletions result in deletion of ‘azoospermia factor regions’ of the Y chromosome. Assisted reproductive techniques (ARTs) can be used if some sperm are present, however, if successful, this may result in male children inheriting the father’s genetic defects (Golan et al., 2021).…”
Section: Causation and Risk Factorsmentioning
confidence: 99%